RNA-seq transcriptome profiling of pigs’ liver in response to diet with different sources of fatty acids - Fanalli, Simara Larissa; Silva, Bruna Pereira Martins da; Gomes, Julia Dezen; Durval, Mariah Castro; Almeida, Vivian Vezzoni de; Moreira, Gabriel Costa Monteiro; Silva-Vignato, Bárbara; Afonso, Juliana; Freitas, Felipe André Oliveira; Reecy, James Mark; Koltes, James Eugene; Koltes, Dawn; et al. (Frontiers in Genetics, 2023)
Pigs (Sus scrofa) are an animal model for metabolic diseases in humans. Pork is an important source of fatty acids (FA) in the human diet, as they represent one of the most consumed meat worldwide. The effects of dietary inclusion of oils such as canola, fish, and soybean oils on pig gene expression are mostly unknown. Our objective was to evaluate FA composition, identify changes in gene expression in the liver of male pigs fed diets enriched with different FA profiles, and identify impacted metabolic pathways and gene networks, to enlighten the biological mechanisms variation. Large White males pigs were randomly allocated to one of three diets with 18 pigs in each: all diets comprised a base of corn and soybean meal to which was added either 3% of soybean oil (SOY); or 3% canola oil (CO); or 3% fish oil (FO) for a 98-day trial during the growing and finishing phases. RNA-sequencing was performed from the liver samples of each animal by Illumina technology for differential gene expression analysis performed using the DESeq2 R package. The diets modified the FA profile, mainly in relation to polyunsaturated and saturated FA. Comparing SOY vs FO, 143 differentially expressed genes (DEG) were identified associated with metabolism, metabolic and neurodegenerative disease pathways, inflammatory processes, and immune response networks. Between CO vs SOY 148 DEG were identified, with pathways related to FA oxidation, regulation of lipid metabolism, and metabolic and neurodegenerative diseases. Our results help explain the behavior of genes with differential expression in metabolic pathways resulting from feeding different types of oils in pig diets.